The Epistle of Salim ibn Dhakwān - Sālim ibn Dhakwān, active 8th century (Oxford University Press, 2001)
The epistle ascribed to Salim Ibn Dhakwan, and written sometime before AD 800, was discovered in the early 1970s by the scholar, Amr Khalifa Ennami, who brought a xerox of the now lost manuscript to the attention of Islamic scholars. The epistle which is here edited, translated, and discussed in full for the first time is an early Islamic tract against `wrong' doctrines regarding the classification and treatment of opponents.
Arabic epistle which is here edited, translated, and discussed in full for the first time.
Keywords: Sālim ibn Dhakwān, -- active 8th century. -- Sīrat Sālim ibn Dhakwān.; Sīrat Sālim ibn Dhakwān (Sālim ibn Dhakwān); Ibadites.; Kharijites.; Murjiʼah.; Islam -- Doctrines.; Shīʻah -- Doctrines.; Ibāḍites.; Khārijites.; Murjiʻah.; Chiisme -- Doctrines.; RELIGION -- Islam -- General.; Ibadites; Islam -- Doctrines; Kharijites; Murjiʼah; Shīʻah -- Doctrines